Extraction, purification, structural characterization, and health benefit of the litchi (Litchi chinensis Sonn.) polysaccharides: a review - Wang, Bo; Bi, Haizheng; Zhang, Mengru; Xu, Xinrui; Wang, Meng (Frontiers in Pharmacology, 2025)
Litchi, a prominent species within the Litchi Sonn genus of the Sapindaceae family, is a fruit renowned for its significant nutritional, health, and pharmacological properties. Polysaccharides are one of the functional active ingredients in litchi, with various biological functions such as hypoglycemic effect, prebiotic effect, promoting effect on exopolysaccharide production by Weissella confuse, antioxidant effect, antiproliferative effect, immunoregulatory effect. Consequently, research on litchi polysaccharides has steadily expanded and deepened in recent years. A comprehensive review of existing studies is essential for advancing the understanding of these polysaccharides. This article provides an overview of the current state of research on litchi polysaccharides, covering various aspects such as extraction, purification, chemical structure, health benefits, and structure-activity relationships. Furthermore, it offers valuable insights to guide the continued development of litchi polysaccharides, establishing a scientific foundation for their more efficient and rational utilization.